Ultrafast Universal Fabrication of Metal‐Organic Complex Nanosheets by Joule Heating Engineering. Issue 1 (25th November 2021) - Xu, Feng; Zhou, Yanping; Zhai, Xingwu; Zhang, Hongjian; Liu, Haodong; Ang, Edison Huixiang; Lu, Yufei; Nie, Zhentao; Zhou, Min; Zhu, Jixin
Abstract: Two‐dimensional metal‐organic complex (MOC) nanosheets are of great interest in various areas. Current strategies applied to synthesize MOC nanosheets are suffering from low yield, usage of large amounts of environmentally unfriendly organic solvent, are time and energy consuming, and cumbersome steps for 2D nanostructures. In this work, a novel joule heating mechanism is proposed to fabricate MOC nanosheets about 5 nm in thickness with tunable metal compositions (i.e. M = Co, CoNi, and CoFe) within 60 s. Small amount of water is used as the only solvent. Under the intense irradiation of the microwave, fast heating via ionic conduction loss is realized, and urea is catalytically condensed into the long‐chain organic ligands rich in N atoms that are capable of coordinating with metal ions to form the stubborn MOC framework, which is simultaneously puffed into an ultrathin nanosheet structure by the intensive release of gas. As a proof of concept, the as‐synthesized Co‐MOC nanosheet exhibits a superior lithium storage performance of 360 and 330 mA h g –1 after 1200 and 2300 cycles at a current density of 500 and 1000 mA g –1, respectively. Abstract : Microwave boosts the ultrafast, universal, self‐adjusted synthesis of metal‐organic complex nanosheets with tunable compositions, which show great potential in lithium‐ion batteries.